2010
DOI: 10.1002/jcc.21665
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular geometry and anharmonic vibrational spectra of thiourea and thiourea‐d4

Abstract: Potential energy surface (PES) of thiourea, SC(NH(2))(2), has been searched for stable conformers under C(1), C(s), C(2), and C(2v) symmetry constraints by post-Hartree-Fock ab initio methods with electron correlation level varying from second-order Moeller-Plesset perturbation theory (MP2) to quadratic configuration interaction with single and double excitations (QCISD) and basis sets of double- and triple-zeta quality within 6-31+G(d,p) to aug-cc-pVTZ range. Thiourea conformers of C(2) and C(s) symmetry have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…40 A further detailed study including anharmonicity was carried out using MP2 and QCISD methods. 44 We are aware of only one theoretical work dealing with the adsorption of thiourea and thioureate (on a Ag(111) surface), authored by Patrito et al, 35 where electric field and solvent effects were considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 A further detailed study including anharmonicity was carried out using MP2 and QCISD methods. 44 We are aware of only one theoretical work dealing with the adsorption of thiourea and thioureate (on a Ag(111) surface), authored by Patrito et al, 35 where electric field and solvent effects were considered.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors studied the vibrational behavior of TU and TU- d 4 by comparing the experimental spectra in argon and nitrogen matrices with their respective theoretical vibrational frequencies obtained at the B3LYP/6-31+G(2d,p) level . A further detailed study including anharmonicity was carried out using MP2 and QCISD methods . We are aware of only one theoretical work dealing with the adsorption of thiourea and thioureate (on a Ag(111) surface), authored by Patrito et al, where electric field and solvent effects were considered.…”
Section: Introductionmentioning
confidence: 99%
“…After its first structure determination by X-ray diffraction, only recently (in 2004) has a microwave spectroscopy study provided a partial gas-phase substitution structure . On the contrary, the vibrational spectrum of thiourea has been widely investigated and characterized (see refs and references therein). While in most vibrational studies bands were assigned assuming for thiourea a C 2 v planar symmetry, ab initio calculations ranging from second-order Møller–Plesset perturbation theory (MP2) to density functional theory (DFT) have shown that only the heavy atom skeleton, NCSN, is planar, and the C 2 conformer, with nonplanar amino groups, is the lowest in energy.…”
Section: Introductionmentioning
confidence: 99%
“…[11,13] The ground and excited state geometry structures of thiourea, one of the simplest thiocarbonyl compounds, and its derivatives were determined from the theoretical calculations and experimental measurements. [1,[16][17][18][19][20][21][22][23] It has been concluded that the geometry structure of thiourea in ground electronic state keeps the coplanarity of N-C(N)=S moiety due to the interaction between the nitrogen lone pairs and the thiocarbonyl p system, while that of thiourea in S 2 (pp*) excited state undergoes the out-of-plane deformation motion or the pyramidalization of carbon in the N-C(N)=S moiety, and the coplanarity disappears. [23] 2-Mercapto-1-methylimidazole (MMI) is a five-member aromatic heterocyclic derivative of thiourea.…”
Section: Introductionmentioning
confidence: 99%
“…Strong chemical interaction was found between the excited states of thione conformer and hydrocarbon solvent in the process of intermolecular photochemistry and photophysics . The ground and excited state geometry structures of thiourea, one of the simplest thiocarbonyl compounds, and its derivatives were determined from the theoretical calculations and experimental measurements . It has been concluded that the geometry structure of thiourea in ground electronic state keeps the coplanarity of N‐C(N)=S moiety due to the interaction between the nitrogen lone pairs and the thiocarbonyl π system, while that of thiourea in S 2 (ππ*) excited state undergoes the out‐of‐plane deformation motion or the pyramidalization of carbon in the N‐C(N)=S moiety, and the coplanarity disappears .…”
Section: Introductionmentioning
confidence: 99%